Modelling Values - BAWA, SAVITA (THE PRIMARY TEACHER, 2014)
During the last Parent Teacher Meeting a parent told me that her son was always watching TV. Another parent said that his daughter was not fond of reading. Still another parent confided in me and discussed at length all the changes that were coming in the thinking and personality of his child. The list can go on endlessly. The problems varied but every parent looked at me expectantly as if I, the teacher, had the magical wand to set everything right. Parents expressed not only their complete helplessness but also the desire to see a positive change in their children. Back home I started thinking: do I really influence the lives of young adolescents this much? Why did the parents have such faith in me? I started introspecting and continued to observe my own behaviour for a period of time. I became mindful of my words and actions. I realized that children learn more by what they see than what they hear. It is easy for them to follow foot prints than advice. I may be able to escape the eagle eyes of my Principal but never my students. It is both verbal and non-verbal language used by me in the class or outside the class that students observe so minutely. I think I am the magician performing live on the stage every day